The Effect of Air Quality and Income Inequality on Health Status in Nigeria (1980 - 2020) - Akintunde, Temitope SAde; Adedokun, Daniel; Aribatise, Adekunle (Acta Universitatis Danubius. Œconomica, 2024)
The World Health Organization (WHO) has implemented numerous economic policies to increase life expectancy, but the results have been disheartening in developing nations, particularly Nigeria. Thus, using Auto regressive distributed lag (ARDL) technique, this study investigated the effect of air quality and income inequality on health status in Nigeria. Annual data over the period of 1980 to 2020 sourced from the World Bank Development Indicators (WDI) were used for the study. The results showed that income inequality and carbon dioxide emissions in Nigeria had significantly influenced life expectancy in Nigeria. Furthermore, income inequality and CO2 emissions lead to significant health loss, particularly in Nigeria. However, improved air quality and reduced income inequality alone are insufficient for sustained good health status. Employment, improved Gross Domestic Product, strong macroeconomic policies, and an efficient institutional setup are equally significant. The study therefore advocates for policy that aid the redistributing income thus improving access to clean household energy by transitioning to cleaner cook-stoves and solar lighting, and improving municipal solid waste management should be put in place.